SDUNet: Road extraction via spatial enhanced and densely connected UNet. (June 2022) - Yang, Mengxing; Yuan, Yuan; Liu, Ganchao
Highlights: We propose a network SDUNet, which combines the multi-level features of the road network and global prior information. A structure preserving model is proposed to enhance feature learning about the structure prior of the road surface. Experimental results show that our approach achieves state-of-the-art performance compared with previous methods. Graphical abstract: Abstract: Extracting road maps from high-resolution optical remote sensing images has received much attention recently, especially with the rapid development of deep learning methods. However, most of these CNN based approaches simply focused on multi-scale encoder architectures or multiple branches in neural networks, and ignored some inherent characteristics of the road surface. In this paper, we design a novel network for road extraction based on spatial enhanced and densely connected UNet, called SDUNet. SDUNet aggregates both the multi-level features and global prior information of road networks by combining the strengths of spatial CNN-based segmentation and densely connected blocks. To enhance the feature learning about prior information of road surface, a structure preserving model is designed to explore the continuous clues in the spatial level. Experimental results on two benchmark datasets show that the proposed method achieves the state-of-the-art performance, compared with previous approaches for road extraction. Code will be made available on https://github.com/MrStrangerYang/SDUNet .